2021
DOI: 10.3390/ani11061707
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti in Rodents from Different Habitats of Lithuania

Abstract: Babesia microti (Aconoidasida: Piroplasmida) (Franca, 1910) is an emerging tick-borne parasite with rodents serving as the considered reservoir host. However, the distribution of B. microti in Europe is insufficiently characterized. Based on the sample of 1180 rodents from 19 study sites in Lithuania, the objectives of this study were: (1) to investigate the presence of Babesia parasites in eight species of rodents, (2) to determine the prevalence of Babesia parasites in rodents from different habitats, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…in rodents varied substantially among the genus/species detected. This variation could be explained by the observed differences in the abundance and diversity of rodents from different sampled habitats, as earlier explained by Mardosaitė et al (2021). Additionally, close contacts between rodent species, humans and other animals in human-related activities may contribute to the variation in prevalence (Islam et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…in rodents varied substantially among the genus/species detected. This variation could be explained by the observed differences in the abundance and diversity of rodents from different sampled habitats, as earlier explained by Mardosaitė et al (2021). Additionally, close contacts between rodent species, humans and other animals in human-related activities may contribute to the variation in prevalence (Islam et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Although rodents (mainly referring to mice) were considered to be the primary intermediate animal host reservoir of B. microti [ 66 , 67 ], its infection has been reported in many kinds of animals including Carnivora (cat, dog, bear), Soricomorpha, Artiodactyla (ibex, cattle), primates, shrews and even birds ( Table 2 and Table S2 ). The wide range of animal hosts and high prevalence in animals might contribute to the worldwide distribution of B. microti .…”
Section: Discussionmentioning
confidence: 99%
“…Rodents are important hosts of many pathogens and play important roles in the conservation, transmission, and prevalence of diseases [ 20 ]. Our previous studies showed that eight species of rodents were found in Southeastern Shanxi, located between the Taihang and Taiyue Mountains, at an average elevation of 900–1000 m. And Bartonella , Borrelia burgdorferi , Leptospira interrogans , Anaplasma phagocytophilum and Orientia tsutsugamushi were detected in rodents in this area [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%